Differenciating Oil, Gas And Water In Seismic Section Using Spectral Decomposition - Suprajitno Munadi; Humbang Purba; Rosie A.S (Scientific Contributions Oil and Gas, 2012)
Oil, Gas And Water Contained In The Pore Spaces Should Give Different Response In The Seismic Trace, But This Is Not An Easy Problem. However, From The Physical Point Of View Oil Is Quite Compressible, Gas Is Very Compressible And Water Is Incompressible, So In Principle They Should Give Different Response In Seismic Â Record. Since The Response In The Time Domain Is Sometimes Complicated In Nature, An Effort Has Been Carried Â Out To Remedy The Problem In The Frequency Domain. A Recent Advance In Signal Analysis Which Is Referred To As The Spectral Decomposition Has Been Used To Differentiate Oil, Gas And Water In Seismic Section. In This Case A Specifi C Method In Spectral Decomposition Called As The Continuous Wavelet Transform (CWT) Was Utilized For This Purpose. The Result Demonstrates That Oil, Gas And Water Can Be Differentiated Clearly In The CWT Spectrum Using The Data From The Deep Water Part In The Makassar Strait. The Results Are Encouraging.Â